Tooth bandits - Hay, Sam (New York, NY Branches/Scholastic Inc, 2016)
Stella hopes to use her magic glasses to see the Tooth Fairy, but instead she sees Piper, the Tooth Bandit, a type of night sprite that steals the coins left for children and uses them to decorate their scooters--so Stella comes up with a different kind of decoration for the bandits
English stories
2
Keywords: Eyeglasses -- Fiction; Fairies -- Fiction